Impacto da implementação de um protocolo de detecção e tratamento precoce da sepse em pacientes transplantados renais admitidos em unidade de terapia intensiva - Cordeiro, Mariana Oliveira [UNIFESP] (2018)
OBJETIVES - To assess the impact of the implantation of a managed protocol for sepsis early detection and appropriate treatment in the lethality of renal transplant patients. METHODS - This is a retrospective, unicentric study. The protocol for early detection and treatment of sepsis was instituted at the Hospital do Rim e Hipertensão (HRIM) in March 2013. The compliance with lactate and blood cultures sampling, early administration of antimicrobials, hemodynamic optimization and mortality was reported to the Latin American Sepsis Institute (ILAS), which sent back to the institution quarterly reports during 21 months. We included patients older than 18 years, with renal transplantation using immunosuppressants, with diagnosis of severe sepsis or septic shock as the reason for intensive care unit (ICU) admission between March 2013 and July 2015. We analyzed data from HRIM and ILAS, in addition to medical records. Continuous variables were described in mean and standard deviation or median and interquartile range from 25-75%, using Pearson's qui-square test, Fischer's exact test or Mann - Whitney nonparametric test as appropriate. RESULTS: We included 149 patients, being 63.1% male, with a median age of 59 years. The lethality of transplanted patients with sepsis or septic shock was 32.2%. Throughout the intervention period, compliance with lactate sampling was 81.8% and with antimicrobial administration within the 1st hour after the diagnosis of sepsis/septic shock was 86.6%. However, the 6-hour bundle compliance was only 6% because of low rates for hemodynamic interventions. Only blood cultures compliance increased progressively throughout the intervention period. There was no increase in 6-hour bundle compliance or reduction in the lethality of sepsis / septic shock patients throughout the intervention. CONCLUSION - It was not showed a reduction in sepsis lethality or an increase in the compliance with the quality indicators of the 6-hour bundle after the implementation of a sepsis managed protocol to treat renal transplanted patients.